Pengaruh Bimbingan Guru PAK Terhadap Disiplin Belajar Siswa Kelas V SD Negeri No.173525 Balige Tahun Pembelajaran 2024/2025 - Tripena Engelina Manullang; Tahadodo Waruwu; Risden Anakampun; Hasudungan Simatupang; Dame Taruli Simamora (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this study was to determine the suspected positive and significant influence of PAK teacher guidance on the learning discipline of grade V students of SD Negeri No.173525 Balige in the 2024/2025 Academic Year. The method used in this study uses a quantitative research method with an inferential statistical descriptive approach. The population is all grade V students of SD Negeri No.173525 Balige in the 2024/2025 Academic Year, totaling 41 people and all of them are used as research respondents. Data were collected using a positive closed questionnaire of 45 items. The results of the data analysis showed that there was a positive and significant influence of PAK teacher guidance on the learning discipline of grade V students of SD Negeri No. 173525 Balige in the 2024/2025 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.628> rtable ( = 0.05, n = 41) = 0.308 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 5.044> ttable ( = 0.05, dk = n-2 = 39) = 2.021 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂=